PENGARUH DIFERENSIASI, PROMOSI DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN LAPTOP MEREK ACER (STUDI KASUS MAHASISWA FAKULTAS EKONOMI UPI YPTK PADANG) - Nichy Oktaviani (STKIP Pesisir Selatan, 2018)
ABSTRACTThis study aims to determine how much influence Differentiation, Promotion and Brand Image on the Decision to Purchase Asus Brand Laptops, this method of data collection is by circulating questionnaires with a sample of 100. The analytical method used is multiple regression analysis. The results obtained are: (a) Differentiation has an effect of 0.297 on purchasing decisions. Then differentiation does not have a positive and significant influence, (b) Promotion has an influence of 0,000 on purchasing decisions. So promotion has a positive and significant influence. (c) brand image has an effect of 0.010 on purchasing decisions. So the brand image has a positive and significant influence, with (d) differentiation, promotion and brand image having an influence of 0,000 on purchasing decisions. So, differentiation, promotion and brand image together have a positive and significant relationship. Finally the author suggests Acer Laptops are expected to increase differentiation by paying attention to the characteristics, values, images and prices in order to satisfy their customers so that they can be enjoyed by the wider community, can improve the promotion of Acer Laptop products so that they are better known by many people and can enhance the brand image Acer Laptop products are those that consist of recognition, reputation, attractiveness and domain.Keywords: Purchase Decision, Differentiation, Promotion, Brand Image